Correlation between cloud cover and gamma rays at ground level in São José dos Campos, SP - Alves , Mauro Angelo; Martin , Inácio Malmonge (Seven Editora, 2023)
Simultaneous measurements made with a one-minute sampling interval of cloud cover at three height levels (250 - 2000 m, 2000 - 6000 m and 6000 - 8000 m) and gamma radiation counts obtained at ground level were carried out in May and June 2014. Results show that there is a degree of correlation between cloud cover and radiation counts. This correlation can be caused by the variation of the local amount of radon-222 gas, or by the production of radiation due to the acceleration of electrons originating from cosmic rays by electric fields inside clouds. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-172